Growth and Population of Daphnia magna fed Powder Spirulina Sp. - Rahman, Abd Arif; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Kelautan dan Perikanan Indonesia, 2022)
This research was conducted in February-March 2021 at the Fish Hatchery and Breeding Laboratory, Aquaculture departement, Faculty of Fisheries and Marine science, Riau University. The purpose of this research was to determine the effect of population growth of Daphnia magna and the best dose of Spirulina sp. flour on population growth of D. magna. This research used an experiment, with a one-factor Completely Randomized Design (CRD) with 5 treatments and 3 replications. With treatment, namely Control, P 0.02 g/L, P 0.04 g/L, P 0.06 g/L, P 0.08 gr/L. Experiment was carried out for 16 days and the population was observed every two days. The results of the research showed that the dose of Spirulina sp. flour had a significant effect (P0.05), the highest results were found in P 0.06 g/L with a total of 1165 ind/L on day 12, then followed by P 0.04 g/L was 953 ind/L on day 10, after that P 0.02 g/L was 716 ind/L on day 8, and the lowest was Control with a total of 655 ind/L on day 8th, temperature ranged from 28,1-29,4 C pH ranged from 7.17.3, DO ranged from 4.5-5.3 mg/L, and ammonia ranged from 0.00458-0.00741 mg/L.Keywords: daphnia magna, spirulina sp., dose